Hubungan Usia, Pendidikan, Beban Kerja Mental, SKS, dan Jam Kerja dengan Stres Kerja Dosen Wanita Universitas Airlangga - Riza Hamdiyah; Noeroel Widjajati; Ayu Prima Kartika (Media Gizi Kesmas, 2023)
Background: Work stress is an emotional, physical and physiological reaction to the damaging or dangerous aspects of work that occur when the demands of the job do not match the worker's abilities. Women have little opportunity to develop in a male-dominated workplace. Female lecturers have a dual role: being responsible as a wife and mother. Stress can be caused by organizational factors including task demands, role demands, interpersonal relationships, career development, work structure, and work climate. Objectives: The purpose of this research is to analyze the relationship between age, education, mental workload, semester credit unit, and work hours with the Work stress of female lecturers at Universitas Airlangga. Methods: This research was an observational study with a cross sectional design. The purpose of this study was to analyze the factors associated with work stress on female lecturers at Airlangga University. This research was conducted in September 2019 - February 2020 using a simple random sampling technique with 97 respondents. Results: The results of this research showed that individual characteristics, including age and education did not correlate with female lecturers' work stress. Mental workload (p=0.000), semester credit unit (p=0.000), and work hours (p=0.000) significantly correlate with the work stress of female lecturers at Universitas Airlangga. Conclusions: The conclusion of this study is that mental workload, semester credits and working hours are the factors that cause work stress among female lecturers at Airlangga University. There is no relationship between education and age with work stress among female lecturers at Universitas Airlangga. Mental workload causes work stress for the respondents. The authors recommend that respondents organize their schedules and determine which schedules should be prioritized first. The respondents are female lecturers with work and domestic roles. It is important to create good social support.